Ancient Synagogues of the Golan - Maʿoz, Zvi Uri (The Biblical archaeologist, 1988)
Cumulative data from excavations and surveys reveal a distinctive "Golan type" synagogue in which cultural influences and traditions of decoration from neighboring areas were blended together and adapted to local conditions and materials.